Listicles and the modern news article: comparing the perceived credibility of listicles and traditional articles among millennial media consumers. Issue 2 (15th March 2019) - Sadri, Sean R.
ABSTRACT: Listicles are a new media phenomenon that appear on virtually every news organization's website (articles that are simply lists or rankings and offer concise details about a topic to readers). This study sought to determine the perceived credibility of listicles among the age group most inclined to read them (millennials). Using a sample population of millennials ( N = 363), participants were randomly assigned to read an article in one of two formats: a listicle or a traditional article. Participants then answered a questionnaire rating the credibility of the article and recalling facts from the story. The experiment found that millennials rated the listicle as significantly more credible than the traditional article. The study also hypothesized that millennials may retain more information from a well-constructed listicle than a traditional article containing the same information, but this hypothesis was not supported. The study results and the implications of these findings are discussed.